Machine or Melody? Joseph Ratzinger on Divine Causality in Evolutionary Creation - Ramage, Matthew J. (Scientia et Fides, 2020)
In a document penned under the direction of its then-president Cardinal Joseph Ratzinger, the Vatican’s International Theological Commission observed that many neo-Darwinian materialists and their Christian critics share a misunderstanding of the nature of divine causality. This article explores the thought of Joseph Ratzinger in view of proposing the features of a path that seeks to eschew these faulty understandings of how God causes evolutionary change within our world, thus providing an alternative to the Intelligent Design movement’s approach to creation. . Ratzinger has a deep respect for the integrity of nature, rejecting the notion that God is a “craftsman” who “tinkers” with the world. According to Ratzinger, evolutionary change occurs “precisely in the processes of a living being” even as human beings are “not the mere product of development.” Finally, the emeritus pontiff insists that creation is an ever-present act that unfolds “in the manner in which thought is creative,” a dynamic that he describes variously as a story, drama, melody, and symphony. Wedding these and other key insights, this article submits that Ratzinger’s thought on evolution should lead us to conceive of creation less along the lines of an intelligently designed machine and more as a masterpiece story that is continually being told as its plot unfolds naturally over the course of time.